Microplastic and metal contamination in Bermuda fishes at different trophic levels - Nathan, Justine Emily (2020)
Marine pollution has attracted increasing attention from scientists and the public in recent years due to its impacts on marine life. Studies have focussed on presence of plastics and metal contaminants in both the water and biota. Links between microplastics and metals in different ares of the environment are often overlooked. Analyses have focussed on many areas of coastal waters and the open ocean but, despite being located within the North Atlantic Gyre, Bermuda has never been studied for plastic presence. Therefore a sequence of impacts of marine pollution were analysed in the water and fishes of Bermuda to provide an overview of the country’s marine pollution situation. Surface trawls were used to determine plastic density in the ocean. This ocean plastic was then evaluated for its bioavailability of metal contaminants. Eight species of fish across three trophic levels were analysed for microplastics present in their guts. Two of these species were selected to investigate the level of metal contaminants in fish tissue. All species and 32% of individual fish contained plastic in their guts. Evidence of biomagnification of microplastics by trophic levels and length was found. Microplastics were confirmed as a vector for metals into fish as they are biovailable on injested microplastic particles. Illegal levels of Cd were found in all fish as well as some containing dangerous Pb and Cr levels. Cd showed a positive correlation with fish length whereas Pb showed a negative one. The presence of plastic and metals across species and trophic levels may pose a threat to their health and consumption of these fish and their predators causes concern of potential impacts on humans. These risks should be evaluated in future studies, focusing on higher trophic levels to improve understanding of the affects of marine pollution on ecosystems and humans. A poluição marinha tem atraído uma atenção crescente de cientistas e do público nos últimos anos devido ao seu impacto ambiental cada vez mais percetível. Um dos exemplos ...